PENGARUH GAYA KEPEMIMPINANDEMOKRATIS DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT.PANIN BANK CABANG ATMO PALEMBANG - Kesuma, Bronto; Syamsuddin, Harun (Jurnal Ecoment Global, 2019)
This study aims to determine the effects of leadership style and motivation on Employee Performance PT. Panin Bank Cabang Atmo Palembang, either simultaneously or partialy. The hypothesis purpose It is suspected that there is an influence between the Democratic leadership style on the Employee Performance of PT. Panin Bank Atmo Branch Palembang. Allegedly there is an influence between Motivation on Employee Performance of PT. Panin Bank Atmo Branch Palembang. It is suspected that there is an influence between the Style of Democratic Leadership and Motivation simultaneously on the Employee Performance of PT. Panin Bank Atmo Branch Palembang. The study population was all employees of PT. Panin Bank Cabang Atmo Palembang which totaled 30 people, the study sample using sampling satured with details of the sample to be tested instrumen and sample data analysis by 37 respondens. From the discussion that has been described, then conclusions can be drawn as follows; The results of testing the research hypothesis there is an effect of Motivation on the Performance of employees of PT.Panin Bank Branch Atmo Palembang, the results of testing the hypothesis that there is no influence of the Democratic leadership style on the performance of employees of PT. Panin Bank Atmo Branch Palembang, and the results of testing the hypothesis that there is an influence between democratic leadership style and motivation together on the performance of employees of PT. Panin Bank Atmo Branch Palembang.Keywords: Style of Democratic Leadership, Motivation and Performance